Development of Self-Access Training Materials for English Proficiency Test Preparation - Rionaldi, Rionaldi; Saputra, Boni (Politeknik Negeri Bengkalis, 2024)
Self-access learning materials are essential for English proficiency test preparation to enhance learners’ success inachieving desired language proficiency levels. This research explores the development of self-access training materials specificallydesigned for English proficiency test preparation. The research method used was Research and Development (R&D) with theADDIE model, which includes analysis, design, development, implementation, and evaluation. Validations from experts in design,content, and language, alongside feedback from students and lecturers, confirmed that the developed training materials metestablished criteria for good quality training materials. The result of this research can later be employed as a resource material forlearners and educators to support learners in achieving required English language proficiency.